THE USE OF BILINGUAL FABLE TO IMPROVE STUDENTS’ VOCABULARY - Nilu Iska Dewi; Nur Asmawati; Hikmatur Rahmah (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2022)
This research aims to find out the improvement of students’ vocabulary after being taught by using Bilingual Fable of the sixth-grade students at SDN 5 Tentena, Poso. The method used in this research was Classroom Action Research (CAR). To analyze the data, the researcher used test, descriptive quantitative analysis. The result of this study shows that in the pre-cycle the student’s average score is 42. In the first cycle the students’ average score is 61, while in the second cycle the students’ average score is 72. From pre-cycle, first cycle and second cycle, the average of the students score is always increasing. It can be concluded that the use of Bilingual Fable as media to improve students’ vocabulary is also able to make students interest and motivate in learning process. Thus, the use of bilingual fable is effective in improving students’ vocabulary.